Evaluation of the role of CD3 and CD8 immunostaining in the diagnosis of mild enteropathy celiac disease - Yousif, N. K.; Al-Haroon, S. S. (Regulatory Mechanisms in Biosystems, 2025)
Celiac disease is a chronic, immune-mediated inflammatory disorder of the small intestine, triggered by gluten ingestion in genetically predisposed individuals. This study aims to investigate the role of CD3 and CD8 immunohistochemical stains in the detection of increased intraepithelial lymphocytes in patients diagnosed with mild enteropathy celiac disease. A cross-sectional study was conducted at Basrah/Al-Sader Teaching Hospital from April 2018 to July 2019. Patients with mild enteropathy celiac disease were selected, and intraepithelial lymphocytosis in duodenal biopsies was histologically evaluated before and after the application of CD3 and CD8 immunostains. A total of 57 patients participated in the study, with a median age of 30 years. Of these, 37 (64.9%) were female, and 20 (35.1%) were male, with a male-to-female ratio of 1:1.8. Routine hematoxylin and eosin staining revealed that 31 cases (54.4%) were classified as Marsh type 0, 19 cases (33.3%) as Marsh type 1, and 7 cases (12.3%) as Marsh type 2. However, the application of CD3 and CD8 immunohistochemical stains led to a reclassification in 27 out of 57 cases (47.4%). Specifically, 17 of the 31 cases (54.8%) initially classified as Marsh type 0 were reclassified as Marsh type 1, while 6 of the 19 cases (31.6%) initially classified as Marsh type 1 were reclassified as Marsh type 0, and 4 of the 7 cases (57.1%) initially classified as Marsh type 2 were reclassified as Marsh type 0. Immunohistochemical staining with CD3 and CD8 plays a crucial role in the evaluation of intestinal biopsies for celiac disease.